2003
DOI: 10.1074/jbc.m304262200
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific Footprinting Reveals Differences in the Translocation Status of HIV-1 Reverse Transcriptase

Abstract: Resistance to nucleoside analogue inhibitors of the reverse transcriptase of the HIV-1 often involves phosphorolytic excision of the incorporated chain terminator. Previous crystallographic and modeling studies suggested that this reaction could only occur when the enzyme resides in a pre-translocational stage. Here we studied mechanisms of polymerase translocation using novel site-specific footprinting techniques. Classical footprinting approaches, based on the detection of protected nucleic acid residues, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
146
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(156 citation statements)
references
References 42 publications
(49 reference statements)
8
146
0
2
Order By: Relevance
“…However, the presence of dNTP substrate can stabilize the complex, which prevents dissociation in the presence of trap. These findings are consistent with site-specific footprinting experiments showing that the nucleotide traps the complex in the posttranslocated state (27,31). Here we used complexes PPTϩ3, as an example for a pre-translocated complex, and PPTϩ6, as an example for a post-translocated complex, to look at the stability of ternary complexes with PFA and the next nucleotide, respectively (Fig.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…However, the presence of dNTP substrate can stabilize the complex, which prevents dissociation in the presence of trap. These findings are consistent with site-specific footprinting experiments showing that the nucleotide traps the complex in the posttranslocated state (27,31). Here we used complexes PPTϩ3, as an example for a pre-translocated complex, and PPTϩ6, as an example for a post-translocated complex, to look at the stability of ternary complexes with PFA and the next nucleotide, respectively (Fig.…”
Section: Resultssupporting
confidence: 72%
“…A related, more complex version of this model has also been proposed for multisubunit RNA polymerases (34,35). Our previous site-specific footprinting experiments with stalled HIV-1 RT complexes revealed that the presence of the templated nucleotide can stabilize and trap the post-translocated complex (27). The next complementary nucleotide facilitates the formation of a stable ternary complex that blocks pyrophosphorolysis and the ATP-dependent excision of chain terminating nucleotides (15,29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations